Flood Disaster: Control and Utilization of Space after the Enactment of the Job Creation Law - Tuharyati, Yanny; Jannah, Ayudha Dhefiatul; Triagustin, Silvi Ana (Journal of Geosciences and Environmental Studies, 2024)
The arrangement of Green Open Space is an area in the form of paths and groupings to its broader benefits; the pathway contains plants that grow naturally or are naturally grown directly. The Spatial Planning Law states that 30% of urban areas must have green areas, with 20% for public space and 10% for private. This study aims to determine the utilization and control of space after the enactment of Law No. 6/2023 on Job Creation in the Jember Regency, especially in urban areas. This research is normative juridical, meaning that it is carried out by examining various kinds of formal legal rules, such as laws, literature, and theoretical concepts, which are then related to the problems that are the subject of discussion.  The approaches used in this research are the statute approach (legislative approach) and conceptual approach (concept approach / expert opinion). The study results explain that Law No. 26 of 2007 concerning Spatial Planning provisions regarding the content, guidelines, and procedures for preparing provincial and district/city spatial plans are regulated in Ministerial regulations. Still, in Law No. 6/2023 Job Creation, there are renewed provisions regarding the content, guidelines, and procedures for preparing provincial and district/city spatial plans regulated in Government Regulations. Based on this description, local government efforts to overcome floods can use several regulatory provisions in the Job Creation Law.